Implikasi Pembentukan Produk Hukum Daerah Terhadap Penertiban Kenderaan Angkutan Becak Motor (Bentor) - Awaludin S. Habibie; Asdar Arti; Rusmulyadi Rusmulyadi (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
The study examines the impact of regional regulations on motorized becak (Bentor) transportation, focusing on Regional Regulation Number 6 of 2006. It finds that while these regulations affect community order and local traditions, they lack adequate legal protection and safety measures for passengers. The research, conducted through empirical normative legal methods, highlights a need for improved legal awareness and enforcement due to numerous traffic violations and Bentor accidents. The study suggests a review of the regulation's substance to accommodate better the unique characteristics and needs of Bentor transportation within Gorontalo Province.